Association of the advanced lung cancer inflammation index and controlling nutritional status score with atrial fibrillation in COPD patients: a multicenter cross-sectional study - Xu, Hao; Zheng, Yanhong; Li, Tianye; Mei, Yao; Yang, Mengya; Chen, Chengshui; Hua, Zhidan; Zhao, Hongjun (Frontiers in Nutrition, 2026)
BackgroundThe coexistence of chronic obstructive pulmonary disease (COPD) and atrial fibrillation (AF) is common and portends a poorer prognosis. This study evaluated whether the Advanced Lung Cancer Inflammation Index (ALI) and Controlling Nutritional Status (CONUT) score—composite biomarkers of inflammation and malnutrition—are associated with AF prevalence in COPD patients.MethodsThis multicenter, cross-sectional study included 1,510 hospitalized patients with COPD. AF was diagnosed according to the European Society of Cardiology (ESC) guidelines, encompassing both a documented clinical history and electrocardiographic evidence. The ALI and CONUT scores were calculated from baseline data. Their independent and combined associations with AF were assessed using multivariate logistic regression, restricted cubic splines (RCS), and analyses of joint groups based on optimal cut-off values. Model performance and improvement were evaluated using the area under the receiver operating characteristic curve (AUC), net reclassification improvement (NRI), integrated discrimination improvement (IDI), and decision curve analysis (DCA). The robustness of the findings was further tested through extensive subgroup and sensitivity analyses.ResultsAmong 1,510 patients with COPD, 425 (28.15%) had AF. After comprehensive adjustment for confounders, both a lower ALI and a higher CONUT score were independently associated with increased odds of AF. A nonlinear, L-shaped relationship was identified for ALI (inflection point: 16.09), while CONUT exhibited a linear, positive association. Patients in the combined “low ALI and high CONUT” group had the highest odds of AF (OR = 2.420, 95% CI: 1.721–3.403). The integration of both indices into the baseline model yielded a statistically significant improvement in discriminative power (AUC: 0.842 vs. 0.835, p = 0.031), accompanied by substantial reclassification improvement (NRI = 0.273, p < 0.001). The findings remained consistent across extensive sensitivity analyses and most clinical subgroups, with a notable interaction observed specifically in patients with pulmonary hypertension.ConclusionLower ALI and higher CONUT scores were significantly associated with a higher prevalence of AF in COPD patients. These readily available composite indices, particularly when used in combination, may aid in identifying patients at increased odds of AF, who could be prioritized for further evaluation.